2012
DOI: 10.1111/j.1445-5994.2010.02261.x
|View full text |Cite
|
Sign up to set email alerts
|

The safety of flexible fibre‐optic bronchoscopy and proceduralist‐administered sedation: a tertiary referral centre experience

Abstract: Background: Flexible fibre‐optic bronchoscopy has become an essential investigation and is widely regarded as safe, but wider published prospective data regarding delayed complications are limited. There is continuing debate concerning the safety of proceduralist‐administered sedation. We evaluated complication rates of bronchoscopy and proceduralist‐administered sedation at our tertiary institution, and their clinical significance. Methods: Prospective evaluation of all patients undergoing bronchoscopy over a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
35
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 19 publications
3
35
0
1
Order By: Relevance
“…Major complications (major bleeding, termination of the examination, intubation, need for ICU or death) were uncommon in both groups. The percentage of 2% was similar to the one described by DANG et al [27] (2.2%) in patients sedated with a benzodiazepine and an opiate.…”
Section: Discussionsupporting
confidence: 71%
“…Major complications (major bleeding, termination of the examination, intubation, need for ICU or death) were uncommon in both groups. The percentage of 2% was similar to the one described by DANG et al [27] (2.2%) in patients sedated with a benzodiazepine and an opiate.…”
Section: Discussionsupporting
confidence: 71%
“…Another noteworthy factor was the absence of complications due to GL during our study. Notably, it can be compared to major adverse events of bronchoscopy in a study by Dang et al in which it was stated that this technique is safe as they came across less major complications like pneumothorax [20]. However, the aim of this study was not to evaluate the efficacy of BAL procedure, there were no major complication of bronchoscopy except desaturation, respiratory discomfort during and throat discomfort after the procedure.…”
Section: Discussionmentioning
confidence: 92%
“…In several countries, mainly in Europe, moderate sedation in endoscopic procedures is restricted only to anesthetists despite several reports on the safety and cost-effectiveness of sedation applied by nonanesthesiologists. [5][6][7] Between the years 2013 and 2014, we performed a prospective observational study that aimed to assess factors that influence anxiety and satisfaction in patients undergoing FB under analgosedation.8 In this brief communication, we would like to present data on the safety of moderate sedation applied by nonanesthesiologists.Patients and methods After obtaining written consent to participate in the study, we enrolled 463 consecutive patients undergoing FB at the Department of Pulmonology of the University Hospital in Krakow, Poland. The exclusion criteria were as follows: respiratory failure (defined as hemoglobin oxygen saturation [SpO 2 ] below 90% despite oxygen therapy or need for more than 50% of oxygen in a respiratory mixture),…”
mentioning
confidence: 99%
“…Some researchers have also suggested that the use of propofol instead of benzodiazepines is preferable because of a more rapid patient's recovery. 9 These drugs proved to be safe in several studies used by nonanesthesiologists, [5][6][7] and are recommended by most gastroenterology and respiratory societies to use for moderate sedation in various endoscopic procedures. 4,10,11 Despite this, anesthesiology societies have raised several safety concerns, especially regarding the use of propofol 12 by nonanesthesiologists, and the use of moderate sedation has not been legally approved in many countries (including Poland), being restricted solely to anesthesiologists.…”
mentioning
confidence: 99%
See 1 more Smart Citation